Temporary employment and digital platform-based work - Unterschütz, Joanna (Temporary employment as an atypical form of employment: No. 19/2022, 2022)
Temporary work and work on digital employment platforms are considered new atypical forms of employment, and the share of workers employed in this way does not exceed 3%. They are similar in the temporary and tripartite nature of employment, as well as the division of the basic functions of the employer between two entities, noticeable also in the case of many platforms. However, temporary employment agencies operate within a legal framework defined at international, European and national level, and with regard to digital employment platforms, this framework is still emerging. However, an unambiguous comparison of both forms of employment and determining the appropriate shape of regulations for digital platforms is hindered by the diversity of platforms’ operating patterns.